Electrochemical Detection of NADH, Cysteine, or Glutathione Using a Caffeic Acid Modified Glassy Carbon Electrode - Lee, P; Compton, R (2013)
A modified electrode was prepared using electrodeposition methods to immobilize caffeic acid (CAF) onto the surface of a glassy carbon electrode (GCE) to create a polymer suitable for biosensor development. The polymer film coverage of the surface bound species was further optimized using electrodeposition methods, thus increasing the surface coverage to ca. 10-9molcm-2. Using cyclic voltammetry, the modified carbon electrode was used to facilitate and observe the electrocatalytic oxidation of coenzymes such as NADH, cysteine, and glutathione at different concentrations. A calibration curve was determined in each case within the concentration range; 300nM to 10mM, with the limits of detection (LOD) of 246μM, 99μM, 2.2μM for NADH, cysteine, and glutathione respectively. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.